2006
DOI: 10.1038/nm1410
|View full text |Cite
|
Sign up to set email alerts
|

Hypomorphic promoter mutation in PIGM causes inherited glycosylphosphatidylinositol deficiency

Abstract: Attachment to the plasma membrane by linkage to a glycosylphosphatidylinositol (GPI) anchor is a mode of protein expression highly conserved from protozoa to mammals. As a clinical entity, deficiency of GPI has been recognized as paroxysmal nocturnal hemoglobinuria, an acquired clonal disorder associated with somatic mutations of the X-linked PIGA gene in hematopoietic cells. We have identified a novel disease characterized by a propensity to venous thrombosis and seizures in which deficiency of GPI is inherit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
159
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(165 citation statements)
references
References 28 publications
3
159
0
3
Order By: Relevance
“…To date, 30 CDG hypoglycosylation defects have been identified, including 17 N-glycosylation defects (13 CDG-I or N-glycan assembly defects and 4 CDG-II or N-glycan processing defects), 6 O-glycosylation defects, 5 combined N-and Oglycosylation defects, and 2 lipid glycosylation defects (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: © 2007 American Association For Clinical Chemistrymentioning
confidence: 99%
“…To date, 30 CDG hypoglycosylation defects have been identified, including 17 N-glycosylation defects (13 CDG-I or N-glycan assembly defects and 4 CDG-II or N-glycan processing defects), 6 O-glycosylation defects, 5 combined N-and Oglycosylation defects, and 2 lipid glycosylation defects (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: © 2007 American Association For Clinical Chemistrymentioning
confidence: 99%
“…6). To date, three cases of PIGM deficiency originating from two families have been described [87]. The patients showed increased thrombosis but no signs of hemolysis, although the levels of several GPI anchored proteins were reduced on hematopoietic cells.…”
Section: Pigm Proteinmentioning
confidence: 99%
“…In recent years, however, complete genome and exome analyses using next generation sequencing have revealed that partial defects in GPI biosynthetic genes may cause disease. To date, congenital GPI deficiencies caused by mutations in PIG-A, PIG-L, PIG-M, PIG-V, PIG-N, and PIG-O have been reported (13)(14)(15)(16)(17)(18). Although the symptoms are different for each gene deficit, epileptic seizure and mental retardation are common symptoms of many congenital GPI deficiencies, and they also present with symptoms such as abnormal facial configuration, cardiac disease, a short phalange, hearing loss, and hyperphosphatasia depending on the mutations in the GPI biosynthetic genes (19).…”
Section: B Gpi Biosynthesis and Deficiencymentioning
confidence: 99%